PENERAPAN PROTOKOL KESEHATAN PADA LAYANAN UPT PERPUSTAKAAN UNTAN DI MASA PANDEMI COVID-19 - Winda, Winda; Madeten, Sisilya Saman (Universitas Tanjungpura, 2022)
AbstractThis study discusses the Application of Health Protocols at the Untan Library UPTServices during the Covid-19 Pandemic. The purpose of the study was to determinethe application of health protocols to Untan Library services and the obstacles facedby the Untan Library in implementing health protocols. This study uses descriptivequalitative methods with data collection techniques, namely observation, interviewsand documentation. The data sources of this research are the head of the library,librarians and users. The results showed that the Untan Library UPT opened allservices during the covid-19 pandemic with the stipulation of health protocols for allservices. So that the service process that takes place is carried out in a different way,namely the obligation to apply 3M (washing hands, wearing masks, maintainingdistance) when entering the library, the process of borrowing collections, returningcollections, using collections in on-site reading services and providing online servicesfor users who will make loan free letter. The obstacles faced are the concerns oflibrarians in serving users during the pandemic, users who do not comply with healthprotocols and users' dissatisfaction with services.Keywords: Covid-19 Pandemic, Health Protocol, Library Service, Service Process.